Five important preventive measures against exacerbation of coronavirus disease - Yamamoto, Kenji (Anestezjologia Intensywna Terapia, 2021)
Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is mainly transmitted through droplets and aerosols [1]. Viral RNA is predominantly detected in the oral and nasal cavities; however, it has also occasionally been detected in stool, urine, and lacrimal samples. Infection prevention through use of masks, handwashing, and social distancing may be challenging. Although a lockdown in urban areas can slow the spread of infection and allow time for preparing an adequate response, it is difficult to determine the optimal time for unlocking and lifting quarantine measures and to prevent further spread once people resume their daily schedules. As the virus is spreading worldwide, in part owing to asymptomatic carriers, the incidence of infection will likely continue to fluctuate until herd immunity is achieved, which may take several months to years [2].